Brazil's Foreign Policy from the context of South-South Development Cooperation initiatives: the case of Brazil and Mozambique after Lula - Correa, Julia (Department of Political Studies, 2021)
South-South Development Cooperation is a longstanding practice that has undergone many unprecedented changes since the dawn of the twenty-first century. However, following the first decade of the century, some key players in development cooperation seem to have reduced their efforts to promote South-South Development Cooperation, notably Brazil. Under president Luiz Inácio Lula da Silva, Brazil's ambitious strategy of international prominence was most eminent within the framework of development cooperation, wherein the African continent occupied a central place. Such efforts, however, lost impetus under the subsequent presidencies of Dilma Rousseff (2011-2016) and Michel Temer (2016-2018). This thesis reflects upon the changes in Brazil's foreign policy dispositions after Luiz Inácio Lula da Silva (2011-2018) and how it affected the country's South-South Development Cooperation initiatives. By looking at the case of Mozambique, it seeks to understand such changes vis-à-vis the shifting nature of both the international system and, most importantly, the domestic setting of Brazil. While the government of Luiz Inácio Lula da Silva laid the foundations of Brazil's South-South Development Cooperation agenda (i.e. an instrument for the pursuit of the country's global ambitions and a reflection of the national approach to development), these foundations were undermined during the subsequent governments, led by constraining international circumstances and the dismantling of the state-led developmental model advanced by the Workers' Party. The undermining of South- South Development Cooperation's foundations occurred through two major mechanisms. Firstly, foreign policy goals were re-defined in economic terms, and so was South-South Development Cooperation. The political goals that underpinned Brazil's reformist ambitions lost space once the latter were gradually abandoned under Dilma Rousseff and completely discarded under Michel Temer. Secondly, South-South Development Cooperation both reflected and fed the model of state-led development adopted by the government of Luiz Inácio Lula da Silva. Once this model was delegitimised and eventually dismantled, the South-South Development Cooperation agenda lost its impetus.